2019
DOI: 10.1016/j.fitote.2019.104272
|View full text |Cite
|
Sign up to set email alerts
|

GIRK channel activity of Hungarian mushrooms: From screening to biologically active metabolites

Abstract: In the current study effects of fungal extracts on the G-protein-activated inwardly rectifying potassium channel (GIRK1/4) were screened using the automated patch-clamp method. 40 organic (n-hexane, chloroform, and 50% methanol) and aqueous extracts were prepared from 10 mushroom species native to Hungary. Among the examined fungal fractions of different polarities some n-hexane and chloroform extracts exerted considerable ion channel activity. One of the most active fungal species, Hypholoma lateritium was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…In recent years, the biochemical properties of G. fusipes have been studied closely in relation to human health. Compounds extracted from G. fusipes have the potential to block G‐protein‐coupled inwardly rectifying potassium (GIRK) channels (Ványolós et al, 2019), the abnormal functioning of which has been linked to cardiac arrhythmia as well as other disorders such as neuropathic pain and drug addiction (Walsh, 2011). Gymnopus fusipes has also been studied in connection with the recently isolated and biosynthesised Gymnopeptides A and B, natural products originally extracted from the species and found to have potential anti‐cancer activities (Ványolós et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the biochemical properties of G. fusipes have been studied closely in relation to human health. Compounds extracted from G. fusipes have the potential to block G‐protein‐coupled inwardly rectifying potassium (GIRK) channels (Ványolós et al, 2019), the abnormal functioning of which has been linked to cardiac arrhythmia as well as other disorders such as neuropathic pain and drug addiction (Walsh, 2011). Gymnopus fusipes has also been studied in connection with the recently isolated and biosynthesised Gymnopeptides A and B, natural products originally extracted from the species and found to have potential anti‐cancer activities (Ványolós et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Gymnopus fusipes fruiting bodies, have typical agaricomycete morphology (Figure 1), are often brown to reddish-brown in colour, and can appear individually, but more often form in small groups at the base of trees and stumps (Marçais et al, 2000b). The distinctive tapering stipe of the species has led to the common name of the spindle-shank mushroom (Ványolós et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…org/10.22201/ib.20078706e.2023.94.5223 traducen en incrementos de insolación, de temperatura, de salinidad del suelo y de una cada vez mayor incidencia de xenobióticos, debido a la cercanía o a la vecindad de estos bosques con áreas agropecuarias y zonas urbanas e industriales (Feckler et al, 2018). Las comunidades fúngicas -y de otros organismos-que habitan en sitios con tales características, han desarrollado estrategias biológicas para adaptarse y sobrevivir en ellas, con mecanismos interesantes para explorar, en la búsqueda de productos bioactivos novedosos o alternativos a los existentes (Anteneh et al, 2019;Thorn et al, 1996;Toledo et al, 2014;Ványolós et al, 2019). Para ello, es necesario aumentar e incentivar los estudios sobre diferentes gremios de hongos, como los saprótrofos, en diferentes tipos de bosques y de ambientes perturbados en México.…”
Section: Introductionunclassified
“…[15] We have recently explored the chemistry of this species and identified a series of steroids with remarkable structural diversity including ergostane and lanostane derivatives, along with highly degraded sterols with ion channel modulating properties. [16,17] As regard the pharmacology of H. lateritium, previous investigations revealed that this species possesses considerable biological properties; however, these experiments were performed with crude extracts without identifying the major fungal metabolites responsible for the observed biological activity. Lee at al.…”
Section: Introductionmentioning
confidence: 99%